ĐÁNH GIÁ HIỆU QUẢ BẢO QUẢN ĐÔNG KHÔ CHỦNG VI KHUẨN VÀ XẠ KHUẨN BIỂN BẰNG KỸ THUẬT TIỀN XỬ LÝ LẠNH SÂU VÀ SỬ DỤNG CHẤT BẢO VỆ - Đỗ, Thị Tuyến; Nguyễn, Thị Kim Thanh; Ngô, Cao Cường; Đỗ, Thị Thu Hồng; Nguyễn, Thu Hoài (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATE THE EFFICIENCY OF FREEZE-DRYING PRESERVATION OF MARINE BACTERIAL AND ACTINOMYCETE STRAINS BY DEEP FREEZING PRETREATMENT TECHNIQUES AND THE USE OF PROTECTANTSThis study aimed to evaluate the effect of deep freezing pretreatment techniques and the protectants on the efficiency of freeze-drying preservation of Bacillus amyloliquefaciens ĐL01.B09 (Genbank OQ415515) and Streptomyces sp. TA3.A03 (Genbank OQ415510) isolated from marine sediments in Truong Sa archipelago (Spratly Islands), Khanh Hoa province. The results showed that the survival rate of both strains ĐL01.B09 and TA3.A03 in the sample pretreatment formula at -80°C was higher than at -20°C and higher than the control without deep freezing pretreatment, the survival rate reached 71% with actinomycetes and 73% with bacteria. When the two microorganism strains were deep freezing pretreatment combined with the use of protectants including lactose, sucrose, trehalose, and skim milk, their survival rates were 51% - 80%, which is significantly greater than the control (21% - 18%). Using a combination of protectants including trehalose 10%, skim milk 10%, sodium glutamate 1% and NaCl 0.9% and deep freezing pretreatment at -80°C provided the best protective effect, the survival rates were 91%-88% and the density of microorganisms after freeze-drying reached ≥ 1010 CFU/mL. The quality of freeze-dried microbial strains met Vietnam's standard TCVN 6168 - 2002 after 15 months of preservation at room temperature.